SOSIALISASI PENDIDIKAN TINGGI GUNA MENINGKATKAN KUALITAS SDM DI SMAN 1 CILELES KABUPATEN LEBAK, BANTEN - Endi Permata; Dzaki Miftah Farid; Muhammad Gibran F (Universitas Pahlawan Tuanku Tambusai, 2023)
It is important to innovate in the educational process so that the knowledge gained will generate people's motivation to improve their economy. Getting a proper education is the right of every individual, so it needs support not only with a strong will but also a stable economy. It is important for every family to set aside the interests of educational expenses. One of the high schools in Prabugantungan Village is SMA Negeri 1 Cileles. The number of Cileles 1 Public High School graduates who are interested in studying at tertiary institutions is still relatively small as shown by the sharp decline in SNMPTN registration. The purpose of this study was to identify and analyze the influence of parents' economic conditions, school environment, and interest in continuing their education to tertiary institutions, both simultaneously and partially. The method of implementing this socialization activity consists of 3 stages, namely the observation stage, the lecture stage, and the discussion stage. It is hoped that this socialization will provide motivation and at the same time help SMAN 1 Cileles students regarding the importance of continuing their education to tertiary institutions to improve quality human resources and is one of the efforts that needs to be made to achieve the desired goals. Keywords: Education, Outreach, Community